2017
DOI: 10.2319/060117-369.1
|View full text |Cite
|
Sign up to set email alerts
|

Treatment changes of hypo- and hyperdivergent Class II Herbst patients

Abstract: Objectives: To determine the relative effects of Herbst appliance therapy in hypo-and hyperdivergent patients. Materials and Methods: The treated group included 45 growing Class II, division 1, patients treated with stainless steel crown Herbst appliances, followed by fixed edgewise appliances. The untreated control group consisted of 45 Class II, division 1, subjects, matched to the treated sample based on Angle classification, age, sex, and pretreatment mandibular plane angle (MPA). Subjects were categorized… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
24
0
3

Year Published

2020
2020
2022
2022

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 32 publications
(27 citation statements)
references
References 31 publications
0
24
0
3
Order By: Relevance
“…In fact, these authors observed that hypo-and hyperdivergent patients benefit from Herbst's headgear effect in the upper maxilla, while hyperdivergent patients exhibited a deleterious backward mandibular rotation. A possible explanation could be that cantilever Herbst appliance with full-coverage stainless steel crowns on the upper and lower first molars was used by Rogers et al [28], while in the present study, a total acrylic splint extending from the first lower molar to the first contralateral molar was used to reinforce the anchorage. Furthermore, another possible explanation for the rotational differences between subjects with different vertical growth patterns could be the orofacial musculature function as patients with weak jaw musculature could exhibit a backward mandibular rotation.…”
Section: International Journal Of Dentistrymentioning
confidence: 79%
See 2 more Smart Citations
“…In fact, these authors observed that hypo-and hyperdivergent patients benefit from Herbst's headgear effect in the upper maxilla, while hyperdivergent patients exhibited a deleterious backward mandibular rotation. A possible explanation could be that cantilever Herbst appliance with full-coverage stainless steel crowns on the upper and lower first molars was used by Rogers et al [28], while in the present study, a total acrylic splint extending from the first lower molar to the first contralateral molar was used to reinforce the anchorage. Furthermore, another possible explanation for the rotational differences between subjects with different vertical growth patterns could be the orofacial musculature function as patients with weak jaw musculature could exhibit a backward mandibular rotation.…”
Section: International Journal Of Dentistrymentioning
confidence: 79%
“…In a previous study, a significant difference of cranial base-mandibular angle was found between hypodivergent, normodivergent, and hyperdivergent patients [28], and the results showed that hypodivergent subjects tend to decrease this angle, while hyperdivergents tend to increase it. In fact, these authors observed that hypo-and hyperdivergent patients benefit from Herbst's headgear effect in the upper maxilla, while hyperdivergent patients exhibited a deleterious backward mandibular rotation.…”
Section: International Journal Of Dentistrymentioning
confidence: 80%
See 1 more Smart Citation
“…Unbehandelt zeigen hyper-und hypodivergente Klasse-II-Patienten völlig unterschiedliche Wachstumsmuster [36]. Im Vergleich mit hypodivergenten Patienten, deren SNA-und SNB-Winkel im Lauf der Zeit immer größer werden, verkleinern sich die Winkel bei hyperdivergenten Individuen.…”
Section: Hintergrundunclassified
“…Studien, in denen unbehandelte Individuen mit Klasse I und Klasse II statistisch miteinander verglichen wurden, konnten eindeutig nachweisen, dass die Klasse II in erster Linie ein sagittales Unterkieferproblem ist [12]. Dabei [25,36]. Das Kinn bewegt sich hier weniger weit nach vorne und nach unten, weil der Unterkiefer eine echte Rotationsbewegung nach hinten ausführt, während er bei unbehandelten Fällen nach vorne rotiert.…”
Section: Hintergrundunclassified